2016
DOI: 10.17535/crorr.2016.0023
|View full text |Cite
|
Sign up to set email alerts
|

Measuring attitudes in the self-employment intention model: methodological considerations

Abstract: Abstract. The paper is based on a statistical model, the construction of which requires determining the independent variables. To determine the predictive ability of different approaches to measuring independent variables, the paper provides an overview of theoretical and research approaches to the research problem. The purpose of the study is to analyze the predictive power of instruments measuring attitudes toward selfemployment as one of the most significant predictors of a career choice according to the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Other studies also confirmed that willingness to take risk positively influences the likelihood of engaging in self -employment (Brown, Dietrich, Ortiz-Nuñez, & Taylor, 2011). Generally, it was agreed that attitude significantly impacts youths' intentions to be self -employed (Mijoč, Stanić, & Horvat, 2016). Table 3 shows that 95.6% of the youths agreed that self -employment development provides job, 85.8% of them agreed that improvement in standard of living is enhanced through self -employment and 76.1% agreed that increase in national income is one of the contributions of self -employed youths to economic growth.…”
Section: Results Table 1: Demographic Characteristics Of the Respondentsmentioning
confidence: 75%
See 1 more Smart Citation
“…Other studies also confirmed that willingness to take risk positively influences the likelihood of engaging in self -employment (Brown, Dietrich, Ortiz-Nuñez, & Taylor, 2011). Generally, it was agreed that attitude significantly impacts youths' intentions to be self -employed (Mijoč, Stanić, & Horvat, 2016). Table 3 shows that 95.6% of the youths agreed that self -employment development provides job, 85.8% of them agreed that improvement in standard of living is enhanced through self -employment and 76.1% agreed that increase in national income is one of the contributions of self -employed youths to economic growth.…”
Section: Results Table 1: Demographic Characteristics Of the Respondentsmentioning
confidence: 75%
“…Attitudes play a critical role in shaping innovation and behaviour of individuals. Self -employment attitudes is defined as attitude towards entrepreneurship as the extent to which people think there are good opportunities for starting a business (Mijoč, Stanić, & Horvat, 2016;Bosma & Levie, 2012). Attitudes is very significant in establishing selfemployment activity within a population and the attitudes relevant includes willingness to bear the level of risk that individuals might be willing to bear and individuals' perceptions of their own skills, knowledge, and experience in business creation (Przepiorka, 2017;Munk, 2016;Simoes, Moreira, & Crespo, 2013;Bosma & Levie, 2012).…”
Section: Attitude Towards Self -Employmentmentioning
confidence: 99%
“…Thus, if selfemployment is more appealing to students, their intention to work for themselves will be high and vice versa (Ismail et al, 2013;Majogoro & Mgabo, 2012). The empirical literature has found a positive and significant association between attitude and self-employment intentions(See; Alharbi, Almahdi, & Mosbah, 2018;Ayalew & Zeleke, 2018;Mahendra, Djatmika, & Hermawan, 2017;Mijoč et al, 2016;Saraih, Aris, Mutalib, Ahmad, & Amlus, 2018). On this background, the study proposes that H1:…”
Section: Literature Reviewmentioning
confidence: 89%
“…This implies that when students' SEIs are high, the greater the chances of pursuing a self-employment career. The empirical literature has proved the direct and indirect impact of TPB constructs on SEIs (Ayalew & Zeleke, 2018;Bosompem et al, 2017;Kolvereid, 2016;Mijoč, Stanić, & Horvat, 2016;Soomro & Shah, 2015). However, despite the moderating effect of self-efficacy as proposed in the theory, research has paid little attention to this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…W innym artykule -Measuring Attitudes in the Self-Employment Intention Model: Methodological Considerations -znajdujemy opis projektu polegającego na poddaniu samozatrudnienia procesowi modelowania pod kątem pomiaru stosunku (postaw, skłonności) do tej formy zatrudnienia 67 . Jego autorzy przedstawili aspekty metodologiczne związane z przebiegiem modelowania.…”
Section: Literatura Zagranicznaunclassified